Raising great kids in a chaotic world a handbook of strategies, examples, and suggestions for educators and parents - Mendler, Allen N. (Lanham Rowman & Littlefield, 2024)
"Raising Great Kids in a Chaotic World: A Guide for Parents and Educators is a resource that offers guidance to the full spectrum of challenges that adults face in raising and teaching children"--
The challenge of raising kids to thrive -- Tips for educators when offering suggestions -- What children need from parents and caregivers -- Paving the road to success -- How to promote responsibility -- Limits, rewards, consequences -- Communicating effectively with your kids -- Helping your kids solve people problems -- What to do when kids push your buttons -- Helping your kids handle stress -- Take good emotional care of yourself -- Conclusion.
Includes bibliographical references and index.
Keywords: Child rearing; Parenting